Advancements in Local Anesthesia Techniques in Dentistry: Management and Risk Communication from Traditional to Modern Technological Methods - Bukhamseen, Nada Jawad; Shabat, Mohammad Ghassa; Alismail, Rabab Ismail; Alshammari, Nahed Jazza; Alqarni, Abdullah Mohammed; Almousa, Najat Rasheed; Alqahtani, Alhanouf Khalied; Alyahya, Turfah Ibrahim (Journal of International Crisis and Risk Communication Research, 2024)
Local anesthesia is the cornerstone of modern dentistry, effectively managing pain from various dental procedures. This review aims to review the various modern techniques of local anesthesia used in dentistry, and complementary techniques. However, traditional methods of local anesthesia including subperiosteal injections, periodontal ligament, and regional nerve blocks, are widely used but often cause discomfort and anxiety in patients. Modern technologies such as computerized devices, The Wand, and Single Tooth Anesthesia (STA), as well as needle-free injection systems such as Jet-Injectors, have provided more precise and less painful options for anesthetizing specific areas. In addition, new techniques such as laser anesthesia, cryotherapy, and virtual anesthesia (VR) are emerging as complementary tools in pain management. This review highlights the evolution of local anesthesia methods and their potential to improve patient comfort.